High pressure promoted dearomatization of nitroarenes by [4+2] cycloadditions with silyloxydienes. Issue 84 (3rd October 2022) - Rkein, Batoul; Coffinier, Romain; Powderly, Marian; Manneveau, Maxime; Sanselme, Morgane; Durandetti, Muriel; Sebban, Muriel; Hamdoun, Ghanem; Oulyadi, Hassan; Harrowven, David; Legros, Julien; Chataigner, Isabelle
Abstract : Simple nitroarenes such as nitronaphthalenes and nitroquinolines smoothly undergo dearomatizing [4+2] cycloadditions with silyloxydienes under 16 kbar. Abstract : Simple nitroarenes such as nitronaphthalenes and nitroquinolines smoothly undergo dearomatizing [4+2] cycloadditions with silyloxydienes under 16 kbar. Highly functionalized 3-dimensional polycyclic adducts bearing a tetrasubstituted carbon centre at the ring junction are obtained in one step from simple raw materials. This unprecedented dearomative Diels–Alder process is performed at room temperature without any chemical promoter, illustrating the exceptional role of high pressure as a physical promoter.